Pengembangan Model Pembelajaran Sosial Emosional Berbasis LMS untuk Penguatan Karakter dan Kecakapan Intrapersonal Mahasiswa PPG dalam Konteks Pendidikan Bisnis - Rachmad Hidayat; Handri Dian Wahyudi; Mohammad Hari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Strengthening character and intrapersonal skills is a key element in the formation of professional educators, especially in the context of the Teacher Professional Education Program (PPG) in the field of business education. This research aims to develop a social-emotional learning model based on the Learning Management System (LMS) designed to improve self-awareness, emotional management, and personal responsibility of PPG students. The research uses a Research and Development approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, but is limited to the initial Implementation stage. The analysis stage was carried out through a literature study and field needs on the importance of social-emotional learning in the PPG curriculum. The design stage involves the preparation of a model structure that includes material elements, reflective activities, and experiential assessments. The development phase resulted in a prototype LMS containing interactive modules, reflection journals, learning videos, and formative quizzes. The initial implementation stage was carried out in small groups to measure initial response, media availability, and substance validation. The results show that this model can facilitate intrapersonal learning in a more independent, flexible, and contextual manner. This model is considered potential as an alternative to strengthening character in teacher professional education in the business sector.